Reproductive dysfunction and associated pathology in women undergoing military training. Issue 5 (17th February 2017) - Gifford, Robert M; Reynolds, R M; Greeves, J; Anderson, R A; Woods, D R
Abstract : Introduction: Evidence from civilian athletes raises the question of whether reproductive dysfunction may be seen in female soldiers as a result of military training. Such reproductive dysfunction consists of impaired ovulation with or without long-term subfertility. Methods: A critical review of pertinent evidence following an extensive literature search. Results: The evidence points towards reduced energy availability as the most likely explanation for exercise-induced reproductive dysfunction. Evidence also suggests that reproductive dysfunction is mediated by activation of the hypothalamic–pituitary–adrenal axis and suppression of the hypothalamic–pituitary–gonadal axis, with elevated ghrelin and reduced leptin likely to play an important role. The observed reproductive dysfunction exists as part of a female athletic triad, together with osteopenia and disordered eating. If this phenomenon was shown to exist with UK military training, this would be of significant concern. We hypothesise that the nature of military training and possibly field exercises may contribute to greater risk of reproductive dysfunction among female military trainees compared with exercising civilian controls. We discuss the features of military training and its participants, such as energy availability, age at recruitment, body phenotype, type of physical training, psychogenic stressors, altered sleep pattern and elemental exposure as contributors to reproductive dysfunction. Conclusions: We identify lines of future research to more fully characterise reproductive dysfunction in military women and suggest possible interventions that, if indicated, could improve their future well-being.